Retorica e utilità in Aristotele / Rhetoric and utility in Aristotle - Bertollini, Adriano (Rivista Italiana di Filosofia del Linguaggio, 2020)
In the present article I try to shed light on the Aristotelian notion of ‘useful’ (Greek ‘sympheron’). The philosopher uses it in the Rhetoric, where he points out that the deliberative oration has the goal of persuading about what is useful or harmful (§1). After a brief explanation of the ancient Greek terms used to mean the useful (§2), I examine (§3) its role – and that of the public discussion about it – within the political community, which is characterized by a particular form of what Aristotle calls ‘utility friendship’, the political friendship. The last paragraph (4) focuses on this type of philia.